IMPACT OF INDIVIDUAL CHARACTERISTICS AND MOTIVATION ON DOCTOR PERFORMANCE AT RSUD CIDERES - Dian Yuka Ananda Noor; Dede R. Oktini; Kania Nurcholisah (UPT Publikasi Ilmiah UNISBA, 2025)
Health is both a right and an investment for all Indonesian citizens. The increasing trend of patients seeking medical treatment abroad reflects a perception of low domestic healthcare quality, particularly concerning physician performance. RSUD Cideres, a type B hospital with full accreditation, reported good physician performance in 2023, yet expectations for healthcare services demand even higher performance. Physician performance is influenced by several factors, including individual characteristics and motivation. This study aims to analyze the influence of individual characteristics and motivation on physician performance at RSUD Cideres while addressing the research gap on how these factors can be strategically managed to enhance healthcare services. A quantitative method with a descriptive-verificative approach was employed. Sampling used purposive sampling, involving 43 physicians who had worked at RSUD Cideres for at least one year. Data were collected through questionnaires and analyzed using IBM SPSS 27. The results show that individual characteristics influence performance by 33%, while motivation contributes 70.1%. Hypothesis testing confirms a significant effect (Sig. <0.005), both partially and simultaneously. These findings highlight the importance of managing individual characteristics and motivation to improve physician performance in regional hospitals.